Clinical profile of non-critical patients with diabetes mellitus hospitalized in the nursery of the University Hospital of the Federal University of Sergipe (Research, Society and Development, 2022)
Diabetes mellitus (DM) is characterized by persistent hyperglycemia and is associated with micro and macrovascular complications and increased morbidity and mortality. Hospital hyperglycemia (HH), defined by fasting blood glucose greater than 140mg/dL, also increases the risk of complications in the hospital setting. The objectives of this study were to evaluate the clinical profile of non-critical patients with DM and non-diabetics hospitalized in the wards of the University Hospital of the Federal University of Sergipe (HU-UFS) and the frequency of HH. It is a cross-sectional study, with convenience sampling with non-critical patients with DM and non-diabetics hospitalized in the wards of the HU-UFS between august and december 2019. Data were collected through a review of medical records and interviews to research participants. One hundred and sixty patients were evaluated. Among these, 140 patients had fasting blood glucose levels measured by admission and were eligible, divided into two groups: Control Group (n=101) and Diabetic Group (n=39). HH was observed in six patients from the CG and 9 from the DG, with Prevalence Ratio (RP) = 3,89 (95% CI 2.2 to 18.6). The frequency of family history for DM, systemic arterial hypertension, dyslipidemia, increased waist circumference and metabolic syndrome was higher in the DG, with statistical significance. Risk factors for dysglycemia were frequent in non-critical patients from HU-UFS and metabolic syndrome, systemic arterial hypertension, family history of DM and increased abdominal circunference were significantly related to diabetic patients. HH was significantly associated with the presence of DM.